Estradiol and zinc-doped nano hydroxyapatite as therapeutic agents in the prevention of osteoporosis; oxidative stress status, inflammation, bone turnover, bone mineral density, and histological alterations in ovariectomized rats - Elghareeb, Mona M.; Elshopakey, Gehad E.; Elkhooly, Tarek A.; Salama, Basma; Samy, Alaa; Bazer, Fuller W; Elmetwally, Mohammed A; Almutairi, Mikhlid H.; Aleya, Lotfi; Abdel-Daim, Mohamed M.; Rezk, Shaymaa (Frontiers in Physiology, 2022)
Osteoporosis (OP) is a serious health problem, and the most popular therapeutic strategy for OP is hormone replacement (estrogen); however, it increases the risk of reproductive cancers. Hydroxyapatite (HA) nanoparticles have a similar chemical structure to the bone mineral component and can be used as a new remedy for OP. This study was designed to investigate the osteoporosis-protective potential of nano zinc hydroxyapatite (ZnHA-NPs) and/or estradiol (E2) combined therapy. A total of 35 adult female rats were assigned into five groups (n = 7): 1) control group; 2) ovariectomized group (OVX); 3) OVX received oral estradiol replacement therapy (OVX/E2); 4) OVX received ZnHA replacement therapy (OVX/ZnHA); and 5) OVX received both estradiol and ZnHA-NPs combined therapy (OVX/E2+ZnHA). After 3 months of treatment, serum bone markers and estrogen level, oxidative/antioxidant, and inflammatory cytokines were determined. Additionally, femoral expression of estrogen receptors alpha and beta (ESR1; ESR2), receptor activator of nuclear factor-kappa B (RANKL) ligand, osteoprotegerin (OPG), bone mineral density (BMD), histological alterations, and immunohistochemical expression of vascular endothelial growth factor (VEGF) and proliferating cell nuclear antigen (PCNA) were assessed. ALP, PINP, Ca, and P concentrations improved significantly (p < 0.05) in all treatment groups, especially in the OVX/E + ZnHA group. MDA and NO were higher in OVX rats, while SOD activity and GSH were lower (p < 0.05). E2 alone or with ZnHA-NPs restored the estimated antioxidant molecules and cytokines toward normal levels in OVX rats (p < 0.05). On the other hand, E2 and ZnHA increased OPG and OC expression in femurs while decreasing ESR1, ESR2, and NF-kB expression (p < 0.05). The combination treatment was superior in the restoration of normal femoral histoarchitecture and both cortical and trabecular BMD (p < 0.05). Overall, the combined therapy of OVX/E2+ZnHA was more effective than the individual treatments in attenuating excessive bone turnover and preventing osteoporosis.